Kontra-punkte: Für 10 instrumente - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2011)
Dress rehearsal, introduction and concert of KONTRA - PUNKTE conducted by Stockhausen( Colour film by Suzanne Stephens ) ( Archive No. 27 / 20 )Dress rehearsal and performance of KONTRA - PUNKTE with introduction, Alte OperFrankfurt, August 22nd 1992 with Ensemble Modern conducted by Karlheinz Stockhausen.